The Interaction Effect of Single NPK Fertilizer with Compound NPK Fertilizer on Growth and Yield of Shallot Plants (Allium ascalonicum L.) - Aisyawati, Lina; Trijaya, Dewi Sekarsari; Robi'in, Robi'in; Arifin, Zainal; Prasetyo, Cahyo; Baskara, Pandu Yunan (Jurnal Hortikultura Indonesia, 2025)
The success of shallot farming is influenced by the availability of high-quality seeds of superior varieties, accompanied by balanced fertilization. NPK fertilizer is important for the growth and development of plants and the yield of shallot bulbs. The experiment was carried out from August to October 2019 in dry land Karangploso Experimental Garden, Assessment Institute of Agriculture Technology (AIAT) of East Java (Malang Regency) during the dry season. This study aims to determine the influence interaction from applying various doses of single NPK fertilizer Urea, ZA, SP-36 and KCl and compound NPK fertilizer against growth and shallot yield. The experimental design used a randomized block design (RBD) arranged factorially (8x3). The first factor is the fertilization package single NPK which consists of two levels, namely: P1= 150 kg ha-1 Urea + 300 kg ha-1 ZA + 150 kg ha-1 SP-36 + 150 kg ha-1 KCl; and P2= 200 kg ha-1 Urea + 500 kg ha-1 ZA + 200 kg ha-1 SP-36 + 200 kg ha-1 KCl. The second factor was compound NPK fertilizer, which consisted of four levels: N0= without compound NPK fertilizer; N1= 100 kg ha-1; N2= 200 kg ha-1; and N3= 300 kg ha-1. The study’s results showed that the treatment of single doses of NPK fertilizer and compound NPK fertilizers did not provide a significant interaction, so these two factors were independent. Keywords: Anorganic Fertilizer, Production, Shallots